Mass appraisal as affordable public policy: Open data and machine learning for mapping urban land values - Carranza, Juan Pablo; Piumetto, Mario; Lucca, Carlos; Da Silva, Everton (2024)
Fil: Carranza, Juan Pablo. Universidad Nacional de Córdoba. Facultad de Ciencias Sociales. Instituto de Investigación y Formación en Administración Pública; Argentina.